(untitled) (Scripta : English Department Journal, 2026)
This study investigates the implementation of the Problem-Based Learning (PBL) model assisted by picture media to enhance students’ critical reading skills in English exposition texts. It addresses the decline in literacy observed during the COVID-19 pandemic and emphasizes the need for innovative teaching strategies to improve student engagement and outcomes. Conducted with class XI-D students at SMA Negeri 1 Purworejo, the research utilized a Classroom Action Research approach over two cycles. The findings revealed a significant improvement in students’ critical reading performance, demonstrating the effectiveness of integrating PBL with picture media. The findings highlight the potential of this method for fostering critical thinking and literacy, particularly in underperforming students. This study contributes to the development of innovative reading instruction strategies that integrate visual media and problem-based approaches to foster students’ critical literacy.